Efficiency in Public-Private Partnership in Management of Steam Power Plant PT. Bosowa Energi - Sirajuddin, Azhari; Ibrahim, Muh. Akmal; Hasniati , Hasniati; Yunus, Muhammad (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study is intended to determine the implementation of efficiency in public-private partnerships in the management of Steam Power Plant PT. Bosowa Energi. Efficiency is a comparison between output and input that describes a company's ability to run operations without wasting resources excessively. The sources in this study are all stakeholders related to Efficiency in Public Private Partnerships in the Management of Steam Power Plant PT. Bosowa Energy. Especially stakeholders involved in the Management of Steam Power Plants in Jeneponto Regency. In this study, the researcher used qualitative​ research to collect related data on The Efficiency of Public Private Partnership in the Management of Steam Power Plant PT. Bosowa Energy in Jeneponto Regency. In this case, PT Bosowa Energy has succeeded in achieving efficiency through the use of the latest technology and maintenance management carried out together with related vendors, such as PT D&C and PT Nalco, which also play a role in maintaining optimal operations. The results of this study indicate that there are obstacles to achieving this efficiency, namely the limited supply of high-carbon coal. Calories which is the main fuel of the Jeneponto PLTU. The supply of this type of coal is increasingly limited because many coal companies prefer to export the coal abroad at a more profitable price. This follows the theory of Hodge & Greve (2007) regarding the challenges in public-private partnerships, where dependence on scarce resources can cause obstacles in achieving efficiency.